2001
DOI: 10.1192/pb.25.7.264
|View full text |Cite
|
Sign up to set email alerts
|

Developing a child and adolescent mental health service for children with learning disabilities

Abstract: Aims and MethodWe discuss the development of a service for children with learning disabilities within a child and adolescent mental health team using the Health Advisory Service Together We Stand tier system. The paper also includes an audit of the service 8 months after it was started.ResultsWe present a model of service that has proved successful to date. We give details from the audit of the service, its aims, funding, referral numbers, sources, types and criteria.Clinical ImplicationsThe audit suggests tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The intellectual disability CAMHS described here exists within a generic CAMHS team. 19,32 This has the advantage of allowing easy networking, joint training, joint working and secondments. It also avoids unnecessary service access issues where different services may not have complimentary referral criteria, leading to service gaps; it therefore provides equity of access within local services, and integrates the team within discussions about new developments and commissioning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intellectual disability CAMHS described here exists within a generic CAMHS team. 19,32 This has the advantage of allowing easy networking, joint training, joint working and secondments. It also avoids unnecessary service access issues where different services may not have complimentary referral criteria, leading to service gaps; it therefore provides equity of access within local services, and integrates the team within discussions about new developments and commissioning.…”
Section: Discussionmentioning
confidence: 99%
“…18 This fits well with our experiences setting up a new service, where after 1 year we had 119 new referrals into the service and were able to discharge only 19 of them in that same period, because of the high levels of need. 19 …”
Section: Existing Mental Health Services For Children With Intellectumentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have found varied results. 18,31 In our study, the symptoms in most cases were noticed between 8-12 years of age, related to academic issues, and were referred by teachers or parents. This might be because of inclusion of the subject of SLD in the modified B. Ed (Bachelor of Education) curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Poorer reading ability is earlier found associated with lower language and cognitive scores. 30,31 On analyzing referral pattern of the children, mean age was found to be 12.9 years, which appears quite late when onset of the disorder per se is viewed. Earlier studies have found varied results.…”
Section: Discussionmentioning
confidence: 99%